The Birth of the Talkies : From Edison to Joison - Geduld, Harry M. (Book collections on Project MUSE., 1975)
From the Preface: Few if any events have had greater impact on the history of film than the coming of the talkies, film historians have paid relatively little attention to how and why the transition from silent to sound cinema came about. It is hoped that the present work will provide the factual groundwork for repairing that neglect. Its emphasis is on the history of American contributions to the evolution of the sound film, but significant foreign achievements have not been overlooked. The book surveys the events that led from the invention of the phonograph in 1877 to that momentous evening in 1927 when an audience at the Warner's Theatre in New York City saw and heard Al Jolson speak from the screen. It also considers the effects of the sound revolution on Hollywood and Hollywood film production during the transitional years 1928-29. The published sources on which this study was based have all been indicated in the notes, and the reader is advised to consult that original material whenever he requires additional technical or factual information.